THE ROLE OF GEOMORPHOLOGY FOR ANALYSIS OF LANDSCAPE ECOLOGY IN THE LONING WATERSHED, KARANGSAMBUNG-KARANGBOLONG NATIONAL GEOPARK - Raharjo, Puguh Dwi (2019)
This location is geologically located in the melange zone due to the subduction of the Australian plate with the Eurasian plate, so that rocks have high diversity. Loning watershed is one of the watersheds located in Karangsambung-Karangbolong National Geopark area. Geopark is an integrated regional concept in protecting geological heritage in a sustainable manner for human welfare. Geodiversity, biodiversity, and culturdiversity are regional elements that aim at conservation, education and tourism. The complex geological process of loning watershed affects geomorphological variation. Every last unit of geomorphological landforms has different characteristics and functions. The purpose of this study was to analyze the geomorphological aspects related to ecology, so that sensitivity to landscape ecology can be obtained for the carrying capacity of the environment in the Geopark Region. The target to be achieved is the creation of geodiversity and biodiversity conservation area management. The research method used uses a laboratory and field approach. Study of laboratory approaches with digital image processing for analysis of vegetation cover with NDVI formula, geomorphological interpretation, river morphometry and other spatial data analysis. Field approach by identifying each altitude segment on biodiversity and geodiversity parameters. The geomorphology in the Loning Watershed is used as a unit of land for landscape ecology. The river order reaches 4 segments, with a level 1 river order amounting to 150. Surface runoff based on the rate of flow density has a value of 4.71 with a bifurcation ratio of 5.73. In the watershed Loning has the characteristics of the river flow through the rock with soft resistance so that the sediment transported by the flow will be greater. The shape of the longitudinal watershed with the peak discharge is long and the decline is also long. Geomorphology is divided into 5 units from upstream to downstream which all have different.